In silico Accuracy and Energy Efficiency of Two Steering Paradigms in Directional Deep Brain Stimulation - Juárez-Paz, León Mauricio (Frontiers in Neurology, 2020)
Background: In Deep Brain Stimulation (DBS), stimulation field steering is used to achieve stimulation spatial specificity, which is critical to obtain clinical benefits and avoid side effects. Multiple Independent Current Control (MICC) and Interleaving/Multi-Stim Set (Interleaving/MSS) are two steering paradigms in commercially available DBS systems. This work investigates the stimulation field steering accuracy and precision, as well as the energy efficiency of these two paradigms in directional DBS. Methods: Volumes of Tissue Activated (VTAs) were generated using pulse widths of 60 µs and five pulse amplitude fractionalizations intended to steer the VTAs radially in 12° steps. For each fractionalization, VTAs were generated with nine predefined target radii. Stimulation field steering accuracy and precision were assessed based on the VTAs rotation angle. Energy efficiency was inferred from current draw from battery values, which were calculated based on the pulse amplitudes needed to generate and steer the VTAs, as well as electrode impedance measurements of clinically implanted directional leads. Results: For radial steering, MICC needed a single VTA. In contrast, Interleaving/MSS required the generation of two VTAs, whose union and intersection created an Interleaving/MSS VTA and an Intersection VTA, respectively. MICC VTAs were 6.8 (-3.2 to 11.8) % larger than Interleaving/MSS VTAs. The Intersection VTAs accounted for 26.2 (16.0 to 32.8) % of Interleaving/MSS VTAs and were exposed to a higher stimulation frequency. Across VTA radii, VTA steering accuracy was 7.0 (4.5 to 10.5) ° for MICC and 24.0 (9.0 to 25.3) ° for Interleaving/MSS, whereas VTA steering precision was 1.0 (0.4 to 1.5) ° and 1.0 (0.0 to 4.0) °, respectively. Pulse amplitudes were 16.1 (9.2 to 28.6) % lower for MICC than for Interleaving/MSS, leading to a 45.9 (18.8 to 72.6) % lower current draw from battery for MICC. Conclusions: The results of this work show that MICC achieves a significantly better stimulation field steering accuracy and has a significantly higher energy efficiency than Interleaving/MSS. Clinical outcomes may profit from the better stimulation field steering accuracy, and longevity of DBS systems may profit from the higher energy efficiency of MICC. However, these findings must be confirmed by clinical studies.